Biblical commentary on the Psalms ; v. 1 - Delitzsch, Franz Julius, 1813-1890; Bolton, Francis (Edinburgh, Scotland T and T Clark, 1873)
Contents : v. 1 : Psalms 1-35. Includes bibliographical references.
Keywords: Bible. O.T. Psalms I-XXXV -- commentaries